22 Assessing altered aortic haemodynamics in patients with bicuspid aortic valves: a novel volumetric quantification of vorticity using 4D Flow. (28th January 2023) - Richards, Caryl E; Parker, Alex; Alfuhied, Aseel; Debeic, Radek; Aslam, Saadia; McCann, Gerry P; Singh, Anvesha
Abstract : Introduction: Altered haemodynamic flow patterns in the aorta are linked with increased risk of bicuspid aortic valve (BAV)-associated aortopathy. 1–3 Using 4D-flow cardiovascular magnetic resonance (4DF-CMR), we assessed whether our novel 3D volumetric quantification of vorticity in the ascending aorta can demonstrate flow alterations of BAV patients from healthy controls with tri-leaflet aortic valves (TAVs), and how this compares to standard 2D in-plane analysis. 4–6 Materials and Methods: 4DF-CMR was performed on 8 BAV (5 male, mean age 55 ± 9 years) subjects without valvulo-aortopathy and 9 TAV controls (3 male, mean age 58 ± 4 years). 3D segmentation of the ascending aorta (from the aortic root to the level of pulmonary artery bifurcation) was undertaken using custom in-house Matlab code. Vortical regions were then identified by the fluid-dynamics-based Lambda2-method where voxels with negative scalar Lambda2 values, derived from the 3D velocity field gradients, are defined as part of the vortex core. Vorticity strength was characterised by time-resolved volumetric calculation of vorticity magnitude. Maximum absolute values at peak systole of the volume averaged velocities, vorticities, and Lambda2 were compared. In-plane peak systolic velocity, flow, and maximum wall shear stress were also quantified on 2D analysis planes at the aortic root and distal ascending aorta using commercial software. Results: Absolute values of 3D peak velocity (321.9 ± 14.2 vs 165.2 ± 38.5 cm/s), vorticity (109.2 ± 25.2 vs 74.0 ± 10.6 rads) and Lambda2 (-709880 ± 316140 vs -262806 ± 69992) were significantly higher (p < 0.001) in the BAV subjects, even after adjustment for age and diastolic blood pressure. While the 2D peak velocity was higher at the aortic root in the BAV subjects (219.3 ± 35.6 vs 136.7 ± 28.3 cm/s, p<0.001), the remaining 2D-derived parameters did not demonstrate significant differences. Discussion: Novel 3D volumetric assessment of 4DF-CMR can differentiate vortical flow patterns between TAV and BAV subjects. The pathologically accentuated vortical flow is a potential mechanism leading to BAV-associated aortopathies. Conclusion: We have demonstrated that volumetric calculations of vorticity metrics using 4DF-CMR may offer novel biomarkers that can quantify pathological haemodynamic patterns in the presence of BAV. References: Ward C. Clinical significance of the bicuspid aortic valve. Heart . 2000;83 (1):81–5. Borger MA, Fedak PWM, Stephens EH, Gleason TG, Girdauskas E, Ikonomidis JS, Khoynezhad A, Siu SC, Verma S, Hope MD, Cameron DE, Hammer DF, Coselli JS, Moon MR, Sundt TM, Barker AJ, Markl M, Della Corte A, Michelena HI, Elefteriades JA. The American Association for Thoracic Surgery consensus guidelines on bicuspid aortic valve-related aortopathy: full online-only version. Journal of Thoracic and Cardiovascular Surgery . 2018;156 (2):e41–e74. Singh A, Horsfield MA, Bekele S, Greenwood JP, Dawson DK, Berry C, Hogrefe K, Kelly DJ, Houston JG, Guntur Ramkumar P, Uddin A, Suzuki T, McCann GP. Aortic stiffness in aortic stenosis assessed by cardiovascular MRI: a comparison between bicuspid and tricuspid valves. European Radiology . 2019;29 (5):2340–9. Richards CE, Parker A, Alfuhied A, McCann GP, Singh A. The role of 4-dimensional flow in the assessment of bicuspid aortic valve and its valvulo-aortopathies. British Journal of Radiology . 2022;Aug 3:20220123. Stankovic Z, Allen BD, Garcia J, Jarvis KB, Markl M. 4D flow imaging with MRI. Cardiovascular Diagnosis & Therapy . 2014;4 (2):173–92. Spartera M, Pessoa-Amorim G, A Stracquadanio A, Von Ende A, Fletcher A, Manley P, S Neubauer S, Ferreira V M, Casadei B, Hess AT, and Wijesurendra RS. Left Atrial 4D Flow MRI: Reproducibility and Temporal Variability. Left atrial 4D flow cardiovascular magnetic resonance: a reproducibility study in sinus rhythm and atrial fibrillation. Journal of Cardiovascular Magnetic Resonance . 2021;23 (29).